NILAI-NILAI PENDIDIKAN AKHLAK DALAM KITAB TAYSIRUL KHALAQ DALAM MENYIKAPI BULLYING DI KALANGAN PELAJAR - Khoirul Badriyah; Ach Faishol; Atika Zuhrotus Sufiyana (VICRATINA, 2022)
This research was made by the author with the aim of knowing what the values ofmoral education in the Taysirul Khalaq book are in addressing the problem of bullyingamong students and to find out what the concept of moral education according toSheikh Hafid Hasan Mas'udi is contained in his book entitled Taysirul Khalaq .Thewriting method used in this study is a qualitative method, more precisely the librarysearch method, which is to examine primary ideas regarding the scope of the problembelieved by relevant second ideas. The main source of this research is the Book ofTaysirul Khalaq by Hafidz Hasan Al-Mas'udi, and also uses second sources, the name isbooks of education, journals and other scientific works that have relevance to thediscussion of research related to the research conducted. The results of the study ofmoral education in the Taysirul Khalaq Book in addressing the problem of bullyingamong students are eight, namely: First, the adab that students must fulfill, nature oftawadhu 'and not being obedient, Second, etiquette in association, Third, Harmony. ,Fourth Brotherhood, Fifth, backbiting and gossip, Sixth, being arrogant or arrogant,Seventh being wrongful or tyrannical. While the concept of moral education accordingto Hafid Hasan Mas'udi in the book Taysirul Khalaq there are five concepts, namely:First, Human Relationships to God, Second Human Relations with Self, Third Teacher and Student Morals, Fourth Maheasy Morals, and Fifth Mazmumah Morals